DIMENSI TRUST DALAM INTERAKSI SOSIAL DI PT PAL SURABAYA MENURUT PERSEPSI MIDDLE MANAGER - jurnalmap map; Indra Prasetyo; Yuventius Sugiarno; Wiyono ÔÇÄ (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This study is to describe the qualitative dimensions of trust from the perspective of PT PAL Surabaya's middle managers. Then to minimize the various conflicts that might arise due to miscommunication and misperception both at the level of middle managers and in influence with top management. In addition, developing mutual expectations to have a trust relationship (mutual trust behavior) between structural levels both in groups (within groups) and within groups (outside groups). The method used in this study is the Focus Group Discussion (FGD). The results showed the most dominant inhibiting factors were lack of confidence, fear, ineffective communication both horizontally and vertically, lack of confidence in team cohesiveness. While the driving factor is the willingness to get to know each other and get the character of a colleague, reciprocity for mutual trust is increasingly developing, trusting with team cohesiveness. Keywords: dimensions of trust, social interaction, perceptions of middle managers